Prevalence and Anthropometric Risk of Metabolic Syndrome in Taiwanese Adolescents. (13th July 2011) - Chu, Nain-Feng; Chin, Hsien-Chuan; Wang, Shu-Chuan
Abstract : Background . To evaluate the prevalence and the importance of anthropometric indexes on metabolic syndrome (MetS) among young adolescents in Taiwan. Methods . We conducted a cross sectional survey to obtain a representative sampling among Taipei adolescents in 2003, totally enrolled of 1, 562 adolescents (764 boys and 798 girls) from age 11 to 15. We used modified NCEP-ATP III criteria to diagnose metabolic syndrome in young adolescents including: blood pressure ≧90th percentile, fasting glucose ≧90th, TG ≧ 90th, HDL-C ≦ 10th, and BMI or WC ≧ 90th according to age and gender specific recommendations. Results . The overall prevalence of MetS was 4.8% for boys and 3.9% for girls. BMI and WC were significantly associated with MetS for both boys and girls, even after adjusting for age, cigarette smoking, alcohol drinking and pubertal status. However, after further adjusting for BMI or WC, WC for boys (OR = 1.14, 95% CI = 1.05–1.24) and BMI for girls (OR = 1.36, 95% CI = 1.13–1.64) were significantly associated with MetS. Conclusions . Adolescents with abnormal BMI or waist circumference had 10 to 20 times higher odds of MetS when compared to normal subjects. Obesity, either general or central adiposity, may play an important role in the development of MetS among adolescents.